Is Preemptive Kidney Transplantation Preferred? Updated Study - Pour-Reza-Gholi, Fatemeh; Nafar, Mohsen; Simforoosh, Nasser; Einollahi, Behzad; Basiri, Abbas; Firouzan, Ahmad; Alipour Abedi, Behrang; Farhangi, Soudabeh (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: For eligible patients with end-stage renal disease, the dialysis stage could be bypassed by preemptive kidney transplantation (PKT), when the organ is available. We compared this treatment option with kidney transplantation in patients with pretransplant dialysis (PTD). Materials and Methods: We retrospectively studied on 300 patients who received PKT between 1992 and 2006 from living donors. They were compared with 300 kidney recipients with PTD matched for the time of transplantation that had been on hemodialysis for at least 6 months. Episodes of rejection, graft function, and graft and patient survivals were compared between the two groups. Results: No significant differences were noted in the sex of the recipients, age and sex of the donors, donor source, and posttransplant immunosuppressive therapy, but posttransplant follow-up was longer (P < .001) and the recipients were older (P < .001) in the PTD group. Seventy-one patients (23.7%) in the PKT group and 64 (21.3%) in the PTD had at least 1 rejection (P = .49). The kidney allografts were functional in 272 (90.7%) kidney recipients in the PKT group and 278 (92.7%) in the PTD group during their follow-ups (P = .30). Five-year graft and patient survival rates were slightly higher in the PTD group, which were not statistically significant (P = .06 and P = .07, respectively). Conclusion: In addition to comparable patient and graft survivals with the PKT and kidney transplantations after a period of dialysis, PKT eliminates hemodialysis costs and complications. We recommend PKT as a better choice for transplantation whenever possible.